(untitled) (Reflection and Critique Law Magazine, 2025)
Constitutional Amendment No. 125 of 2022 introduced significant changes to the Brazilian legal system, particularly regarding the role of the Superior Court of Justice (STJ) in the formation of precedents and the unification of jurisprudence. This study analyzes the consequences of this amendment, focusing on the new requirement of relevance for the admission of special appeals. Initially, the study examines Constitutional Amendment No. 125 of 2022 and the relevance requirement, highlighting the increased discretion granted to the STJ in selecting cases to be judged. Next, it investigates the STJ’s role in forming precedents, from simple precedents to significant ones, emphasizing the importance of consistent jurisprudence for legal certainty. Finally, it discusses the possibility of "state-level" precedents in State Courts and Regional Federal Courts, analyzing the challenges and implications of this dynamic. This study aims to contribute to the understanding of the new role of the STJ in forming precedents and the challenges of maintaining unified jurisprudence in the post-EC No. 125/2022 scenario.